Adherent basal plate myometrial fibers in the delivered placenta as a risk factor for development of subsequent placenta accreta. Issue 12 (December 2015) - Linn, Rebecca L.; Miller, Emily S.; Lim, Grace; Ernst, Linda M.
Abstract: Background: Placenta accreta is implantation of chorionic tissue directly upon the myometrium without normal intervening decidua. The clinical significance of myometrial fibers attached to the basal plate (BPMYO) has yet to be fully elucidated. Objective: To determine the importance of depth and quantity of BPMYO in predicting subsequent accreta in the next pregnancy. Method: Women with placentas from two successive pregnancies submitted for pathologic evaluation were included. 50 cases had clinical and/or pathologic diagnosis of accreta in an index pregnancy. 100 controls had no evidence of accreta in an index pregnancy. H&E slides were re-reviewed and stage of accreta/BPMYO was determined. The stages were defined as: Stage 0-no BPMYO; Stage 1-BPMYO with intervening decidua; Stage 2 < 2 decidual cells separating myometrium from chorionic tissue; Stage 3-accreta; Stage 4-increta; Stage 5-percreta. The amount of BPMYO for each placenta was quantified. Results: Prior placentas of cases were twice as likely to have BPMYO compared to controls (84%vs42%, P  < 0.001). The frequency of stage 1 BPMYO was not significantly different between the two groups (46%v40%, P  = 0.489), but cases were more likely to have higher stages of BPMYO (stage 2–3) in a prior placenta (38%vs2%, P  < 0.001). A significantly higher number of BPMYO foci and a larger proportion of BPMYO on the basal plate (6.2%vs0.7%, P  < 0.001) in cases compared to controls. Conclusions: Small amounts and low stage BPMYO (stage 1) may be common; however, higher stages of BPMYO (stage 2–3) and greater quantities of BPMYO in a delivered placenta are significantly associated with the subsequent development of accreta. Highlights: Prior placentas of patients with accreta examined for basal plate myometrial fibers (BPMYO). High stage BPMYO in prior placenta is associated with accreta development. Greater quantities of BPMYO in prior placenta is associated with accreta development. BPMYO in a prior placenta may assist with predicting accreta in the next pregnancy.